Mathematics: Examples of Sum of products equal to sum of products

Wednesday, April 20, 2016

Examples of Sum of products equal to sum of products

For all integers A, B, C, D, the sum of products, (A-B)*(C+D) + (B-D)*(A+C) is equal to the sum of products (A+B)*(C-D) + (A-C)*(B+D) Example 1: Let A = 11, B = 7, C = 5, D = 3 (A-B)*(C+D) + (B-D)*(A+C) = (11-7)*(5+3) + (7-3)*(11+5) = 4*8 + 4*16 = 32 + 64 = 96 (A+B)*(C-D) + (A-C)*(B+D) =... Sign in to see full entry.

Previous: Quotation about teaching math. - New Entries - Next: If x+y = x y = 3, then what is x^3 + y^3?

Headlines (What is this?)

Referrals - About Us - Press - Terms of Use - Privacy Policy - Conduct Policy
Copyright © 2018 Shaycom Corporation. All rights reserved.